2008
DOI: 10.1089/lap.2007.0173
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Patient Weight and Anesthetic Technique on CO2 Excretion During Thoracoscopy in Children Assessed by End-Tidal CO2

Abstract: There is a significant increase in EtCO(2) in children undergoing thoracoscopy, which is higher than during laparoscopy. Changes in EtCO(2) are larger in smaller children undergoing single-lung ventilation. Thoracoscopy may preserve intraoperative thermoregulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
16
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 8 publications
3
16
0
1
Order By: Relevance
“…These effects may be reduced by using lower insufflation pressures. It has been demonstrated that small children eliminate relatively more CO 2 during pneumoperitoneum or pneumothorax and thus require scrupulous anesthetic management [10,11]. Breath CO 2 could originate from metabolically produced CO 2 or from absorption of insufflation gas.…”
Section: Discussionmentioning
confidence: 99%
“…These effects may be reduced by using lower insufflation pressures. It has been demonstrated that small children eliminate relatively more CO 2 during pneumoperitoneum or pneumothorax and thus require scrupulous anesthetic management [10,11]. Breath CO 2 could originate from metabolically produced CO 2 or from absorption of insufflation gas.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are instances where extra vigilance is required. Younger, smaller children have been shown to have larger changes in EtCO 2 and/or CO 2 elimination during both laparoscopy [11] and thoracoscopy [8]. Neonates are therefore particularly vulnerable.…”
Section: Discussionmentioning
confidence: 99%
“…Coupled with impaired ventilation, this can lead to a marked increase in end-tidal CO 2 (EtCO 2 ) in children undergoing thoracoscopy, which is generally higher than that seen during laparoscopy and in smaller children undergoing single lung ventilation [8].…”
mentioning
confidence: 99%
“…Anestezistin yapacağı en iyi yol hiperventilasyondur. Torakoskopi esnasında masif karbondioksit absorbsiyonu sonucu nörotoksik etkiler gözlenmiştir (9,10) . Laparoskopide karın içi basıncın artmasıyla böbrek fonksiyonları etkilenebilmektedir.…”
Section: Yenidoğanın Endoskopik Cerrahiye Uyumuunclassified